Psychological well being and religious involvement in university students in Lima - Escudero Nolasco, Juan Carlos (2017)
This study aims to establish the relationship between the psychological well being and the religious involvement and to find out the differences in the psychological well being among the different forms of religious involvement. The sample was composed of 297 students from a public university in Lima city. The psychological well being scale for adults (BIEPS, for its Spanish acronym) adapted to the Peruvian context was used to collect the data and a questionnaire created by the author. The results showed that there was no relationship between the psychological well being and the religious involvement. However, we found out that the psychological well being is significantly higher in the group with high religious involvement, which has active participation in religious groups, as well as in the projects component, in contrast to students with other levels and types of religious involvement.